NILAI LOKAL SEBAGAI MODEL MEDIASI PERDATA DI INDONESIA - Zuhri, Lahmuddin; Syaifuddin, Endra (Veritas et Justitia, 2017)
Indonesian society in general does not view land only as economic capital, but perceive the value of land more from a cultural-ecological religious perspective. How land is valued from this perspective and the way it influences method of land dispute settlements at the local level may be used to develop alternate models of land dispute settlement at the national level.  A legal anthropological approach is used here to examine mediation as the basic approach to settle land disputes.  The main argument here is that mediation, which put forth local wisdom, consensus building with full society participation, should be prioritized in developing alternate methods of land dispute settlements.